The Dynamics of Constitutional Provision for the Sovereignty of States in the Post-Soviet Space: The Experience of Tajikistan - A. D. Gafurzoda; J. M. Zoir (Теоретическая и прикладная юриспруденция)
This article examines the issue of constitutional provision for the sovereignty of states in the post-Soviet space, using the Republic of Tajikistan as a case study. Despite the centuries-long history, development, and transformation of the concept of sovereignty, it still requires reflection and specification, and in the context of globalization, also protection and implementation.